(untitled) (Journal of Pathology of Nepal, 2019)
Background: Tumors of lung are common in Nepal. The risk of malignancy has to be judged prior to surgery for which bronchoscopy is often done. Brocho-alveolar lavage and bronchial biopsy are routine procedure done for diagnosis of lung cancer during bronchoscopy. This study was done to correlate the cytology of broncho-alveolar lavage specimen with histopathology in malignant tumors of the lug in our setup. Materials and methods: This study was conducted at department of pathology, Nobel Medical College from August 2017 to December 2018. Histopathology reports with malignancy were compared to their cytological diagnosis. Results: A total of 141 cases were included in the study. Among the study population, Bronchogenic carcinoma was found more prevalent in female. The sensitivity, specificity, positive predictive value, negative predictive value and overall accuracy of broncho-alveolar lavage in the diagnosis of lung cancer were 88.1%, 97.98%, 94.7%, 95.1% and 95.03% respectively. Conclusions: Brochoalveolar lavage cytology has a greater accuracy for the diagnosis of lung cancer; however, benign cases need regular follow up as there are false negative cases.